825 Local Excision Versus Total Mesorectal Excision Following Neoadjuvant Chemoradiotherapy for Rectal Cancer. a Systematic Review and Meta-Analysis. (19th August 2022) - McLoughlin, Morgan; Creavin, Ben; Early, Helen; McCullough, Peter; Cooke, Fiachra; Neary, Peter
Abstract: Aim: Total mesorectal excision with or without neoadjuvant chemoradiotherapy remains the gold standard treatment for rectal cancer. This systematic review aims to establish if Local Excision (LE) in conjunction with neoadjuvant therapy can be used to improve morbidity and functional outcomes without significantly impacting oncological outcomes. Method: A systematic review and meta-analysis was performed using the PRISMA guidelines. All studies comparing neoadjuvant chemoradiotherapy and local excision versus TME were included from 2000 to 2020. Primary endpoint included local recurrence rates. Secondary outcomes included distant recurrence, disease free survival and overall survival. Subgroup analysis was performed on randomised control trials (RCT). Results: Of the 9 studies included, 2 were RCTs. A total of 1161 patients underwent neoadjuvant chemoradiotherapy and surgical excision (LE n=252, TME n=909). Local recurrence was 10% in the LE group compared to 7% in the TME group (OR 0.60, 95% CI 0.33–1.09, p=0.09). Furthermore, there was no significant difference in distant metastasis (OR 1.37, 95% CI 0.84–2.26, p=0.21), Disease Free Survival (DFS) (OR 1.08, 95% CI 0.65–1.82, p=0.76) or Overall Survival (OS) (OR 1.14, 95% CI 0.56–2.35, p=0.71). In subgroup analysis of RCTs, local recurrence rates of 7.2% were seen in the LE group compared to 6.6% in the TME group (OR 0.90, 95% CI 0.34–2.43, p=0.84). Conclusions: Neoadjuvant chemoradiotherapy and local excision is oncologically safe in select patients. A higher non-significant local recurrence rate was seen in the LE group; however, this may be due to heterogeneity in patient selection. Similar local recurrences and oncological outcomes were verified in the RCTs.